Personal Learning Environments (PLE) in a distance learning course on mathematics applied to business - Bidarra, José (2014)
This paper argues that the dominant form of distance learning that is common in most e-learning systems rests on a set of learning devices and environments that may be outdated from the student’s perspective, namely because it is not supportive of learner empowerment and does not facilitate the efforts of self-directed learners. For this study we gathered and examined data on student’s use of Personal Learning Environments (PLEs) within a course on Mathematics Applied to Business offered by the Portuguese Open University (Universidade Aberta). We base the discussion on aspects that characterize student’s conceptions of PLEs, the emergence of connectivism as a new account of how learning occurs in a networked global environment, and conclude that an important goal of online course design should be to let students explore what the emergent Web 2.0 tools have to offer in distance learning. The widespread adoption of PLEs, bringing together learning from different contexts and sources of learning, shows that students are capable of expression in different forms, generating an added-value to distance learning environments.